Genome Sequence of the Bacteriocin-Producing Oral Probiotic Streptococcus salivarius Strain M18 - Heng, Nicholas C. K. (American Society for Microbiology, 2011)
Streptococcus salivarius is a Gram-positive bacterial commensal and pioneer colonizer of the human oral cavity. Many strains produce ribosomally synthesized proteinaceous antibiotics (bacteriocins), and some strains have been developed for use as oral probiotics. Here, we present the draft genome sequence of the bacteriocin-producing oral probiotic S. salivarius strain M18.